The Clinical Outcomes of Monolithic Zirconia and Porcelain Fused to Metal in the Posterior Teeth - Muhammad Afzal Khan, Nuzhat Ayub, Nasir Ali, Palwasha Rauf, Kaisar Khan, Sajid Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate and compare the clinical outcomes and patient satisfaction associated with monolithic zirconia(MZ) and porcelain fused to metal (PFM) crowns in posterior teeth. Material & Methods: A cross sectional study was conducted amongst 120 patients restored with either MZ (n=60) or PFM (n=60) crowns in posterior teeth. Clinical assessment was done using Modified United State Public Health Service (Modified USPHS). Patient satisfaction was measured using a 10 questionnaire based on a 5-point Likert scale. Data were analyzed using SPSS 23.0 version. A p-value <0.05 was considered statistically significant. Results: Monolithic zirconia showed a significantly better outcomes in marginal adaptation (p<0.01), fracture resistance (p<0.01) and esthetic (p<0.05) as compared to PFM crowns. Zirconia restorations also showed a higher patient satisfaction score especially regarding comfort, appearance and hygiene. PFM crowns exhibit more frequent chipping and marginal discoloration as compared to zirconia. Conclusion: This study concluded that Monolithic Zirconia crowns showed a superior clinical performance and patients satisfaction than PFM crowns in posterior teeth. Keywords: Monolithic zirconia, porcelain-fused-to-metal, posterior teeth, crown survival, patient satisfaction.